Pengembangan Desa Wisata Nglanggeran: Pendekatan AHP - Metry Sukma Br Perangin-Angin; Florentinus Nugro Hardianto (Seminar Nasional Penelitian dan Abdimas, 2023)
This study aims to identify and analyze the priority development strategies of Nglanggeran Tourism Village, Patuk, Gunung Kidul. The data collection method used in this study is a field survey using questionnaires and interviews as tools. The sampling technique used is purposive sampling. The sample in this study consisted of 10 informants. The data analysis tool used in this study is the Analytic Hierarchy Process (AHP) with the help of Expert Choice software. There are three main findings in this study. First, the top three influential factors are community empowerment, support from the community/village organizations, and support from the local community. Second, the top three supporting parties are the tourism village management, local community, and the government and related agencies. Third, the top three development strategies are developing existing potentials, developing infrastructure, and following the principles of a tourism village. Keywords — tourism village, influential factors, supporting parties, development strategies